Predictors of improved functional outcome in elderly inpatients after rehabilitation: a retrospective study - Naruishi K (Dove Medical Press, 2014)
Koji Naruishi,1,2 Akiko Kunita,3 Katsuyuki Kubo,1,2 Toshihiko Nagata,4 Shogo Takashiba,2,5 Seiji Adachi1 1Division of Local Care Center, Tottori Municipal Hospital, Tottori, Japan; 2Department of Periodontics and Endodontics, Okayama University Hospital, Okayama, Japan; 3Division of Rehabilitation, Tottori Municipal Hospital, Tottori, Japan; 4Department of Periodontology and Endodontology, Institute of Health Biosciences, Tokushima University Graduate School, Tokushima, Japan; 5Department of Pathophysiology-Periodontal Science, Okayama University Graduate School of Medicine, Dentistry and Pharmaceutical Sciences, Okayama, Japan Purpose: The number of elderly inpatients has been steadily increasing worldwide. However, the ability to predict the degree of improvement of functional capacity after comprehensive examination of elderly inpatients is still lacking. The purpose of this study was to investigate the predictors of improved functional outcome after rehabilitation of elderly inpatients.Methods: We performed a retrospective cohort study with 1,079 patients (age <70 years: N=331, age ≥70 years: N=748) who had been admitted to Tottori Municipal Hospital. Functional Independence Measure (FIM) scores were measured both at admission and discharge to calculate FIM gain and efficiency. Of these patients, 262 patients had oral examinations on admission. The Mann–Whitney U-test or chi-square test was used for statistical analyses. Conditional logistic regression analysis was used to compute the odds ratio (OR) and 95% confidence interval (CI). Cut-off values of FIM scores to determine if elderly inpatients were able to return home after discharge were determined using a receiver operating characteristic curve.Results: FIM scores, including FIM gain and efficiency, of elderly patients were significantly lower than those of middle-aged patients. Inability to close the lips and dysfunctional tongue movement, but not the loss of teeth, were correlated with a reduced improvement of FIM scores. Cognitive impairment and aspiration pneumonia, but not cerebrovascular disease, were also correlated with a reduced improvement of FIM scores. Interestingly, FIM scores were significantly lower in patients with both cerebrovascular disease and a loss of posterior occlusion. Factors shown to have a significant impact on the improvement of FIM scores included the stable posterior occlusion (OR: 2.23, 95% CI: 1.2–4.1), closed lips (OR: 5.15, 95% CI: 2.3–11.7), functional tongue movement (OR: 5.74, 95% CI: 3.0–11.0), presence of cognitive impairment (OR: 0.31, 95% CI: 0.17–0.49), and presence of aspiration pneumonia (OR: 0.27, 95% CI: 0.15–0.51).Conclusion: Age and disorder of oral function may be significant predictors of improved functional capacity after rehabilitation for elderly inpatients. Keywords: elderly inpatients, Functional Independence Measure (FIM), oral examination, geriatric disease